Strategies for Integrating Local Liquor Products into Modern Trade Channels to Enhance the Economic Sustainability of Community Enterprises - Sapsanguanboon, Watcharapoj; Kuasang, Kittirat; Chandrangsu, Shutchada; Sawangphol, Narumit; Jeerasongsakul, Pornrisha; Sathapattayanon, Pichit; Paopthip, Muncharee; Juduang, Rangsan; Pookpan, Usa (Journal for Strategy and Enterprise Competitiveness, 2024)
This research examines the development of local liquor as a quality local product to enhance market expansion opportunities and increase sales for local entrepreneurs. The objectives of the study are: 1) to analyze the external and internal environments affecting local liquors, 2) to develop a business model tailored for local liquors, and 3) to propose guidelines for enhancing the potential of local liquors to penetrate modern trade markets. This qualitative research involved data collection through in-depth interviews. The study found several strengths in the business environment, including the use of raw materials sourced from the community or purchased from local suppliers, brand diversity, and attractive, modern packaging. However, weaknesses were also noted, such as issues with quality control and the lack of product development to enhance quality. The research highlighted threats including regulatory challenges, competition, and weather-related factors. On the other hand, opportunities were identified in business expansion, collaboration, participation in trade fairs, and the potential to grow the business through modern trade. To upgrade the potential of local liquor for modern trade, the study suggests elevating the original Sakthong Phrae liquor, a best-seller, to a premium grade, developing health-oriented formulas, and building a strong brand by emphasizing the brand’s story and creating a distinct product identity. These strategies are expected to facilitate business expansion into both domestic and international markets, enhancing the economic sustainability of community enterprises.